Supervisi Akademik di Era Pembelajaran Abad – 21 di SDN Balerejo Kecamatan Tlogomulyo Kabupaten Temanggung - Gati Destiyani (Journal on Education, 2024)
SDN Balerejo carries out academic supervision in the independent curriculum to improve teacher performance. The aim of this research is to describe and analyze the planning, implementation, evaluation and follow-up of the principal's academic supervision in improving teacher performance in the independent curriculum at SDN Balerejo. The research method is qualitative. Data collection techniques are interviews, observation and document study. Data analysis includes data collection, data reduction, data display, conclusion drawing/verification. Validity test uses triangulation techniques. The research results show that academic supervision planning is carried out cooperatively, creatively, comprehensively, flexibly and continuously. 2) implementation of academic supervision through a coaching paradigm. 3) evaluation of academic supervision is delivered in general and in accordance with supervision principles. 4) follow-up to academic supervision in the form of providing motivation, coaching and solutions. The research conclusion is that the principal's academic supervision including planning, implementation, evaluation and follow-up can improve teacher performance in the independent curriculum in the 21st century learning era at SDN Balerejo.